2017
DOI: 10.5897/ajar2016.11840
|View full text |Cite
|
Sign up to set email alerts
|

Yield and yield components of potato (Solanum tuberosum L.) as influenced by planting density and rate of nitrogen application at Holeta, West Oromia region of Ethiopia

Abstract: Four different nitrogen levels and four plant spacing were studied in 4×4 factorial arrangements in randomized complete block design with three replications. The highest yield, number of tuber, number of tuber and dry weight of tuber were obtained with application of jointly 100 and150 kg/ha nitrogen. Increasing plant density resulted in higher tuber yield, dry weight of tuber and total dry matter yield. Increasing nitrogen fertilizer rate 100 up to 150 kg/ha increased mean tuber weight and total dry matter yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…Potatoes have relatively shallow root zone and lower tolerance for water stress compared to other crops, therefore irrigation may be required where rainfall is limited (Makani et al, 2013). Fayera (2017) confirmed that increasing the rate of nitrogen increase total tuber yield/plot average tuber weight, marketable tuber weight, unmarketable tuber weight, total tuber number/ plant and small tuber size. In agreement with this, finding of Biruk (2018) reported increasing the rate of nitrogen from 0 to 92 Kg/ha linearly increased shoot dry biomass yield.…”
Section: Effects Of Mineral Nutrients On Growth and Yield Of Potatomentioning
confidence: 54%
“…Potatoes have relatively shallow root zone and lower tolerance for water stress compared to other crops, therefore irrigation may be required where rainfall is limited (Makani et al, 2013). Fayera (2017) confirmed that increasing the rate of nitrogen increase total tuber yield/plot average tuber weight, marketable tuber weight, unmarketable tuber weight, total tuber number/ plant and small tuber size. In agreement with this, finding of Biruk (2018) reported increasing the rate of nitrogen from 0 to 92 Kg/ha linearly increased shoot dry biomass yield.…”
Section: Effects Of Mineral Nutrients On Growth and Yield Of Potatomentioning
confidence: 54%
“…Effect of increasing plant population per hectare on potato has revealed high increment on the yield of the crop as reported by Ref. [ 11 ]. And then, providing adequate plant density and amending low soil fertility by applying inorganic fertilizer should be considered to address problems among potato production.…”
Section: Introductionmentioning
confidence: 59%
“…It is a nutrient that can frequently limits yield and quality of potato crop [ 8 ]. Insufficient available N leads to reduce growth and reduce light interception [ 10 ], limits yields [ 6 ] and early crop senescence [ 11 ]. Excessive available N can result in reduced yields [ 12 ] especially, in late-maturing varieties [ 13 ]; delayed tuber set and reduced tuber dry matter content [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current study is inline with Zelalem et al, (2009) who reported that nitrogen and phosphorus at a rate of 207 and 60 kg ha -1 increases plant height by 24 cm and 10.5cm respectively. Similarly, Israel et al, (2012), Alemayehu et al, (2015) and Fayera, (2017) and have found that increasing the application of nitrogen and phosphorus signi cantly increased plant height of potato.…”
Section: Soil Laboratory Analysismentioning
confidence: 81%